PEMINATAN SISWA DALAM KEGIATAN EKSTRAKURIKULER DI SMPN 6 POLEWALI MANDAR - Suwardi, Miftahu Rahmi; Arismunandar; Ansar, Ahlun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the imbalance in student interest and enthusiasm for extracurricular programs at SMPN 6 Polewali Mandar, caused by suboptimal program planning, inconsistent scheduling, and limited infrastructure. This study aims to comprehensively describe student interest in extracurricular activities and identify its supporting and inhibiting factors. A descriptive qualitative approach was employed, involving direct observation, in-depth interviews with key informants, and documentation. Data analysis followed the Miles and Huberman model, comprising data collection, data reduction, data display, and conclusion drawing/verification. The results indicate that student interest, analyzed through five indicators (attraction, enthusiasm, activeness, consistency, and desire to develop abilities), is generally sufficient but remains unevenly distributed. Supporting factors driving this interest include personal hobbies, parental support, positive peer influence, and guidance from advisors. Conversely, the primary inhibiting factors consist of physical fatigue after regular school hours, long commuting distances, erratic weather conditions, inadequate facilities, and poor program management. To optimize student participation, it is practically recommended that the school management map student interests at the beginning of the academic year, restructure the scheduling to be more flexible, and optimize budget allocation for infrastructure improvements.